2008
DOI: 10.1002/pssc.200780166
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of band gap states electrical properties in poly‐Si TFTs by the analysis of the transient currents

Abstract: Nanoarchitecturing of carbon nanospheres onto the surface of activated carbon (AC) gives birth to a new composite carbon material that features a hierarchical structure with macro‐ and nanometer dimensions of the respective carbon components and exhibits a remarkably enhanced adsorption capability for heavy‐metal ions (${\rm CrO}_4^{2 - }$ and Fe3+) from aqueous solution as compared to AC. Thus, we first propose that nanoarchitecturing of AC can be utilized not only as a flexible method for the synthesis of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(25 reference statements)
0
0
0
1
Order By: Relevance
“…Studies analyzing the DOS distribution of oxide semiconductors using light have been conducted using various methods [18][19][20][21][22]. Several research groups have reported the threshold voltage shift and subthreshold voltage swing (S/S) slope of oxide TFT as a function of light intensity [23][24][25]. The donor-like states of oxide semiconductors have also been studied as a characteristic of photocurrent changes depending on the wavelength of light [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the DOS distribution of oxide semiconductors using light have been conducted using various methods [18][19][20][21][22]. Several research groups have reported the threshold voltage shift and subthreshold voltage swing (S/S) slope of oxide TFT as a function of light intensity [23][24][25]. The donor-like states of oxide semiconductors have also been studied as a characteristic of photocurrent changes depending on the wavelength of light [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Στη δεύτερη περίπτωση που αντιστοιχεί σε θετικό σήμα, η μέτρηση πραγματοποιείται μετά τη μετάβαση της πύλης από ισχυρή σε ασθενή αναστροφή (undershoot)[77]. Το σήμα στη περίπτωση αυτή οφείλεται στη σταδιακή εκπομπή των ηλεκτρονίων από καταστάσεις στο πάνω μισό του ενεργειακού χάσματος[95]. Φάσματα DLTS για διατάξεις σε υμένια 30nm Σχήμα 7.10: Φάσματα DLTS για διατάξεις σε υμένια 50nm Σχήμα 7.11: Φάσματα DLTS για διατάξεις σε υμένια 100nm πάχους 30 nm με προσανατολισμό πύλης που επιβάλλει τη κίνηση των φορέων παράλληλα στη διεύθυνση των φραγμών δυναμικού.Όπως απεικονίζεται στο σχήμα 8.2 η δημιουργία κενών πυριτίου εντοπίζεται εντονότερη προς τη πίσω διεπιφάνεια του υλικού ενώ αρκετά σημαντική και η δημιουργία κενών οξυγόνου στο διηλεκτρικό της πύλης.…”
unclassified